Performance of rotated phase shift keying modulation over Ricean fading channels - Özyurt, S; Kucur, O; Altunbas, I (IEEE, 2005)
The performance of PSK modulation over fading channels can be improved by resorting diversity techniques such as space, time, frequency, and modulation diversity. In this paper, the modulation diversity is used to improve the performance of PSK modulation over fading channels. Modulation diversity can be achieved by rotating the signal constellation and using component interleaving. We show that rotated signal constellations with the component interleaving improve the performance of M-PSK modulation (M=2,4,8) significantly as compared to the unrotated ones over Ricean fading channels. For example, when the ratio of the direct path power to the multipath signal power, K is 0 and 10, 9 dB and 2 dB gains are obtained respectively at a symbol error probability of 10(-3) for 8PSK modulation. We also show that as K gets larger, the gain obtained by the rotation rapidly decreases.
2nd International Symposium on Wireless Communications Systems (ISWCS 2005) -- SEP 05-07, 2005 -- Univ Siena, Siena, ITALY
Keywords: modulation diversity; M-PSK modulation; Ricean fading channels